THE PROSPECTS FOR WINE TOURISM AS A TOOL FOR RURAL DEVELOPMENT IN ARMENIA-THE CASE OF VAYOTS DZOR MARZ - Harutjunjan, Arman; Loseby, Margaret (Economics of Agriculture, 2011)
The paper examines the prospective role which wine tourism could play in the rural and in the much needed overall economic development of Armenia. It begins with a brief description of the antique origin and the present economic situation of the wine sector in Armenia, followed by a description of recent trends in the tourist sector as a whole in Armenia. The particular features of wine tourism are examined in relation to Armenia and to other wine producing countries. Attention is then concentrated on a specific region of Armenia, Vayots Dzor, which is particularly important for wine production, and is also endowed with historical monuments with great potential for the development of tourism. The case of one particular village is illustrated in some detail in order to indicate how tourism in general, and specifically wine tourism could be developed for the benefit of the rural community. The paper concludes by outlining a strategy to be followed to achieve the growth of the sector.